2016
DOI: 10.1007/s13164-016-0300-9
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Folk Moral Realism

Abstract: Moral realists believe that there are objective moral truths. According to one of the most prominent arguments in favour of this view, ordinary people experience morality as realist-seeming, and we have therefore prima facie reason to believe that realism is true. Some proponents of this argument have claimed that the hypothesis that ordinary people experience morality as realist-seeming is supported by psychological research on folk metaethics. While most recent research has been thought to contradict this cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…By now, the fact that people are pluralists with regard to their commitment to moral objectivity has been well established. Indeed, a good case can be made that the results of earlier studies which suggested that people are objectivists should be re-interpreted as supporting the view that people are meta-ethical pluralists (Pölzler, 2017a). This pluralism manifests itself in several dimensions:…”
Section: Experimental Findings: An Overviewmentioning
confidence: 94%
See 1 more Smart Citation
“…By now, the fact that people are pluralists with regard to their commitment to moral objectivity has been well established. Indeed, a good case can be made that the results of earlier studies which suggested that people are objectivists should be re-interpreted as supporting the view that people are meta-ethical pluralists (Pölzler, 2017a). This pluralism manifests itself in several dimensions:…”
Section: Experimental Findings: An Overviewmentioning
confidence: 94%
“…Nonetheless, as I will argue in the present section, given the actual dialectic of the meta-ethical debate, such findings are not completely mute, so to speak. An influential type of argument which several meta-ethicists have advanced does purport to derive metaphysical conclusions on the basis of a claim about folk judgments: the so-called 'experiential' or 'presumptive' argument in support of moral realism (e.g., Brink, 1989;Shafer-Landau, 2003; for criticisms, see Kirchin, 2003;Loeb, 2007;Sinclair, 2012;Pölzler, 2017a). Since experiments about folk moral objectivism touch upon the adequacy of this claim about folk judgments, they also touch upon the adequacy of the presumptive argument in support of realism.…”
Section: The Metaphysics Of Moral Judgmentmentioning
confidence: 99%
“…In a number of studies, Wright and her collaborators (Wright, Grandjean, & McWhite, 2013;Wright, McWhite, & Grandjean, 2014) used slight variations of probes constructed by Goodwin and Darley (2008). However, in response to published criticisms of these measures (e.g., Beebe, 2015;Pölzler, 2017Pölzler, , 2018, Wright (2018) has more recently developed a new measure of folk moral objectivism, in which participants were asked to indicate which of the following options best represented a number of situations of moral disagreement between them and another person: 10 Goodwin and Darley (2008) observed some similar patterns in the composite scores they calculated using the tasks described above: participants were more likely to give what Goodwin and Darley consider to be objectivist responses when (i) they were responding to moral judgments than when responding to statements about social conventions or tastes, (ii) participants held stronger opinions about the moral issue in question, (iii) participants perceived there to be less societal disagreement about the issue, and (iv) the moral judgments concerned wrongdoing rather than good or morally exemplary actions.…”
Section: IImentioning
confidence: 99%
“…However, for normative discourse about reasons, it yet needs to be shown that response-dependence views eliminate the constitutive element of that practice. 18 In fact, there is evidence that metanormative beliefs of ordinary people are not clearly committed to robust realism; rather, they exhibit a pluralistic pattern (for a discussion, see Pölzler 2017). For instance, Sarkissian et al (2011) found that people's beliefs about the objectivity of moral facts are culturally bound and correlate with how open people are to alternative perspectives.…”
Section: Prospects For a Non-revisionary Response-dependence Account mentioning
confidence: 99%